Análise das estratégias mercadológicas de uma loja de eletrodomésticos na cidade de Parintins-AM: um estudo de caso - Lira, Israel Reis (Brasil, 2025)
The Marketing area is fundamental for the growth of companies, especially in a scenario full of social, economic and social changes. This study's main objective is to analyze the marketing strategies adopted by an appliance store located in the city of Parintins-AM. The methodology used comprised a descriptive research, with the main approach being quantitative and qualitative research. As for the technical procedures, a bibliographical research, a field research, a case study and a survey were carried out. The results demonstrate that the company invests heavily in the marketing mix, seeking to align them with market changes, with the customer profile, with the intention of satisfying their needs and desires. The marketing strategies consist of the variety of products, advertising through radio and TV advertisements and leaflets; excellence in customer service; promotions carried out during commemorative dates. Thus, it can be concluded that marketing is a fundamental area for companies in contemporary times, as its actions aim to attract and retain customers, increase sales and profits, and add value to its brand in the face of competition.